SEHATI’s Contribution (Free Halal Certification) For Medium and Small Enterprises (MSE) in Indonesia - Sari, Yunita Ratna (Prodi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Ponorogo, 2023)
Introduction: Indonesia has great potential in developing the halal industry sector such as halal food, fashion, cosmetics, pharmaceuticals, tourism, media, financial services which will reach IDR 4,375 trillion so that it can support national economic growth as well as become a role model for the halal industry in Indonesia. But in fact, Indonesia as the largest consumer country of halal food is not the largest producer of halal products. So, that free halal certification is needed so that Indonesia becomes the number 1 exporter of halal products in the world. Research Methods: literature study and then analyzed by analytical descriptive analysis. Results: SEHATI's contribution to UMK in Indonesia, namely 1) accelerating the halal certification procedure, 2) MSEs in managing halal certification are free of charge, 3) the halal certification process can be carried out online using the Sihalal and Pusaka applications to make it easier to take care of halal certification. Conclusion: SEHATI contributed For Medium and Small Enterprises (UMK) in Indonesia, because it could raise the profitability, trust and satisfaction consumers and guaranteed quality of product.